Lightweight Secure Directed Diffusion for Wireless Sensor Networks - Eric Ke Wang; Yuming Ye; Xiaofei Xu (International Journal of Distributed Sensor Networks)
We propose a lightweight secure routing scheme for wireless sensor networks, which provides authenticity and integrity in the routing process with relative low overhead by extending directed diffusion protocol with secure measures. We analyze the security capabilities and performance of our scheme; besides, we execute a simulation and the performance results are encouraging.